1995
DOI: 10.1080/02757549508037689
|View full text |Cite
|
Sign up to set email alerts
|

Studies On the Effect of Hexachlorocyclohexane On the Growth and Silk Qualities of Silkworm,Bombyx MoriL

Abstract: Toxicity of an organochloride insecticide, hexachlorocyclohexane (HCH) on the alterations in the growth and silk qualities of silkworm, Bombyx mori L were investigated. HCH yielded higher growth constants (K), indicating impairment of growth of silkworms and silk gland. The decrement in fibroin content is significant. HCH treatment also resulted in considerable reduction in the cocoon, pupal and shell weights, survival and emergence of pupae and number of eggs laid and deterioration in quality and quantity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Jiequn et al (2019) reported that Chlorfenapyr (8% ME) treated mulberry leaves fed to silkworms 15 and 30 days after spray exhibited a cocoon shell ratio of 19.06 and 18.09 per cent, respectively. Bhagyalakshmi et al (1995) studied the effect of Hexachlorocyclohexane (HCH) on silkworms and reported a considerable reduction in cocoon weight and cocoon shell ratio due to HCH treatment.…”
Section: Cocoon Shell Ratiomentioning
confidence: 99%
“…Jiequn et al (2019) reported that Chlorfenapyr (8% ME) treated mulberry leaves fed to silkworms 15 and 30 days after spray exhibited a cocoon shell ratio of 19.06 and 18.09 per cent, respectively. Bhagyalakshmi et al (1995) studied the effect of Hexachlorocyclohexane (HCH) on silkworms and reported a considerable reduction in cocoon weight and cocoon shell ratio due to HCH treatment.…”
Section: Cocoon Shell Ratiomentioning
confidence: 99%
“…Organochloride insecticides, like Hexachlorocyclohexane, were reported to cause a decrease in fibroin content, pupal weight and fecundity as well as deterioration in quality and quantity of silk thread in B. mori (for detail see Bhagyalakshmi et al, 1995;Li et al, 2010).…”
Section: Hormone Analogues In the Silk Research Fieldsmentioning
confidence: 99%
“…However, the survival of silkworm has been significantly affected by organophosphorus (OP) insecticides such as phoxim [O,O‐diethylO‐(alpha‐cyanobenzylideneamino)phosphorothioate], which can enter mulberry plantations by aerial application and water currents (Nath, ; Li et al, ), resulting in a threat to sericulture, a more than 30% reduction in raw silk, decreased acetylcholinesterase gene expression, and oxidative stress in B. mori (Li et al, ; Peng et al, ; Yu et al, ). In addition, toxicity of the organochloride insecticide, hexachlorocyclohexane (HCH), on damage to the growth of silkworms and silk quality has also been investigated (Bhagyalakshmia et al ). However, the mechanisms involved in the reduction of raw silk caused by OP insecticide exposure are still unknown.…”
Section: Introductionmentioning
confidence: 99%